OPTIMIZATION FOR METHOD IN DETERMINATION OF CHLOR CONCENTRATION IN PM2,5 USING EDXRF EPSILON 5 - Sri Royani; Muhayatun Santoso; Diah Dwiana Lestiani; Dyah Kumala Sari; Anni Anggraeni (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2018)
OPTIMIZATION FOR METHOD IN DETERMINATION OF CHLOR CONCENTRATION IN PM2,5 USING EDXRF EPSILON 5. Airborne particulate matter with aerodynamics diameter less than 2.5 µm, PM2.5, is one of air pollutant parameter which have adverse impacts for human health and environment. To minimize those adverse impacts, elemental composition of PM2.5 needs to be characterized so that can be estimated their sources. One of instruments for characterize PM2.5 is Energy Dispersive X-Ray Fluorescence (EDXRF) spectrometer. EDXRF was used for measuring the elemental composition of PM2.5 in Indonesia. This study focused in determination of chlor concentration in PM2.5 since the optimal condition of chlor quantification using EDXRF spectrometer has not been obtained yet, whereas chlor is one of key element which is needed for source identification of air pollution. Concentration of chlor were determined using calibration curve and sensitivity curve methods. Both of curves were performed using Micromatter standards. The multi-element International Atomic Energy Agency (IAEA) reference materials were used for evaluating the accuracy and precision of the procedure. Our measurements result showed good agreement between observed value and certified value. Their accuracy and precision are more than 90%, to ensure the reliability of analytical results, the comparison with the Particles Induced X-ray Emission (PIXE) results from the same samples were also carried out. The result showed that there was good correlation between EDXRF and PIXE results, this is evidenced by the value of R2 is 0.9592. It can be concluded that calibration curve and sensitivity curve can be used to quantify of chlor in PM2.5 accurately.